2012
DOI: 10.1016/j.pain.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Too sick for school? Parent influences on school functioning among children with chronic pain

Abstract: Parental responses to children with chronic pain have been shown to influence the extent of the child’s functional disability, but these associations have not been well-studied in relation to children’s pain-related school functioning. The current study tests the hypothesis that parental pain catastrophizing and parental protective responses to child pain influence the extent of school impairment in children with chronic pain. A mediational model was tested to determine whether parental protective behaviors se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(148 citation statements)
references
References 51 publications
6
141
1
Order By: Relevance
“…Four studies reported a correlation between parent catastrophizing and functional ability, 19,29,36,45 with links between parent catastrophizing and child attributes in parent-adolescent dyadic relationships, pain catastrophizing by both members of the dyad correlated with functional disability, 19 with more than 70% of the dyads having a concordance in catastrophizing. Among nonconcordant dyads, the dyad with low levels of parent catastrophizing and high levels of adolescent catastrophizing was highly correlated with functional disability than the dyad with the reverse.…”
Section: Environmentmentioning
confidence: 99%
“…Four studies reported a correlation between parent catastrophizing and functional ability, 19,29,36,45 with links between parent catastrophizing and child attributes in parent-adolescent dyadic relationships, pain catastrophizing by both members of the dyad correlated with functional disability, 19 with more than 70% of the dyads having a concordance in catastrophizing. Among nonconcordant dyads, the dyad with low levels of parent catastrophizing and high levels of adolescent catastrophizing was highly correlated with functional disability than the dyad with the reverse.…”
Section: Environmentmentioning
confidence: 99%
“…Additionally, the current study examined the buffering role of two specific teacher support dimensions. Future research may benefit from including multiple informants and more objective indicators (e.g., reports of child absence/academic performance obtained from the school/teacher/parent) as well as other types of support (e.g., pain-specific coping support [60] from various support providers including teachers, parents [37] and peers [29,50].…”
Section: Severity Of Pain In Relationship To School-related Functionimentioning
confidence: 99%
“…Social anxiety disorder was particularly common in the pediatric FAP patients and may contribute to school absence and withdrawal from social activities, thereby perpetuating painrelated disability. 51 A decade after the seminal work by Campo et al, 13 these data underscore the importance of a biopsychosocial approach to FAP that includes screening for anxiety and depression. Future research should evaluate whether interventions that treat mental health problems in FAP improve abdominal pain outcomes.…”
Section: Discussionmentioning
confidence: 98%